Comparison of the Static Balance, Strength and Flexibility Characteristics of the University Students Who Taken Artistic Gymnastic Lesson - Ömer Özer; Recep Soslu (Selcuk University, 2019)
The aim of this study is to examine the effects of a training program specific to Artistic Gymnastics branch on the performance of university students. 72 university student studying in the School of Physical Education and Sports were participated in the study voluntarily as a control and experiment group. The experimental group was given artistic gymnastics training program for 12 weeks, 2 days a week and 60 minutes. For the data obtained, the homogeneity of the normality variance was tested and then the mixed ANOVA analysis was used to determine the difference in the pretest and posttest. When the flamingo balance values were examined, a significant difference was found between the groups (F(1, 71)=4.93, ƞ2 =.07, p lt;.05). A difference in post-test flexibility scores and pre-test scores (F(1, 71)=7.81,ƞ2 =.10, p lt;.05), a significant difference was found between the posttest scores and the pretest scores in strength values (F(1.34, 95.46) =40.69,ƞ2= .36, p lt;.05). As a result, it is thought that the extra training done in gymnastics lesson increases the success of the lesson and it is thought that this type of training will increase the success level in all applied lessons, not only for the gymnastics class.